METHODOLOGICAL APPROACHES TO ASSESSING THE LEVEL OF MANAGEMENT OF ECONOMIC SECURITY OF ENTERPRISES - VYTVYTSKA, Olha; SLYVINSKA, Oksana (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article presents the results of research on the generalization and formation of the main provisions of methodological approaches to the assessment of the level of management of the economic security of enterprises in accordance with modern globalization changes. Criteria for assessing economic security have been determined. It is noted that the development of the system of criteria and parameters characterizing the degree of protection of the enterprise from negative influences is based on a number of proposed principles. The comparative characteristics of the methods of quantitative assessment of the level of threats based on the conditions of application, assessment, accuracy of assessment, costs, accounting for the impact of individual threat factors have been carried out. It is justified to use an approach that reflects the principles and conditions of program-target management and development, which is based on the integration of a set of indicators that determine economic security, to assess the economic security of the enterprise. It was concluded that in an effort to assess the state of such a complex technical and economic system, which is a modern enterprise, which functions in the conditions of the interaction of many internal and external factors, which often have an unpredictable effect on the process of development, production and sale of products, only based on formalized calculations can lead to results that are completely inconsistent with the real state of the enterprise and its development prospects. The proposed model of the interaction of components for assessing the level of management of economic security of enterprises, as a basis for making appropriate management decisions. as well as assessments of the company’s priorities based on the analysis of the state of the level of economic security of the company. In order to adapt the process of economic security management to changing conditions, it is necessary to carry out an effective analysis of solving tasks aimed at improving the functioning of the enterprise.